2022
DOI: 10.1097/wco.0000000000001126
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive methods to monitor intracranial pressure

Abstract: Purpose of reviewIntracranial pressure (ICP) is determined by the production of and outflow facility of cerebrospinal fluid. Since alterations in ICP are implicated in several vision-threatening and life-threatening diseases, measurement of ICP is necessary and common. All current clinical methods to measure ICP are invasive and carry the risk for significant side effects. Therefore, the development of accurate, reliable, objective, and portal noninvasive devices to measure ICP has the potential to change the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Previous studies found that reducing ICP may increase the survival rate among patients with bacterial meningitis [15], which emphasizes the importance of early detection and intervention for ICH. During the neonatal period, Doppler ultrasonography, cerebral blood flow velocity, and near-infrared spectroscopy are common approaches for evaluating ICP [16][17][18][19]. However, the accuracy of these approaches remains problematic, and thus these methods have little validation for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that reducing ICP may increase the survival rate among patients with bacterial meningitis [15], which emphasizes the importance of early detection and intervention for ICH. During the neonatal period, Doppler ultrasonography, cerebral blood flow velocity, and near-infrared spectroscopy are common approaches for evaluating ICP [16][17][18][19]. However, the accuracy of these approaches remains problematic, and thus these methods have little validation for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique is an invasive procedure, is costly and is restricted to some cases of acute brain injuries. Moreover, it is associated with complications and risks, mainly infection, hemorrhage and obstruction [ 9 , 10 , 11 ]. As BD is a condition of perfusion collapse because of extremely high ICP, one rationale on its monitoring could be the ICP waveforms (ICPW), considering that ICPW change according to reduction in intracranial compliance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is an invasive procedure, costly and restricted to some cases of acute brain injuries. Moreover, it is associated with complications and risks, mainly infection, hemorrhage, and obstruction [9][10][11]. As BD is a condition of perfusion collapse because of extremely high ICP, one rationale on its monitoring could be the ICP waveforms (ICPW), considering that ICPW change according to reduction in intracranial compliance [12].…”
Section: Introductionmentioning
confidence: 99%